Students' sitting posture and patterns in Universiti Teknologi MARA Pahang / Muhamad Iqbal Ahmad Bostaman - Ahmad Bostaman, Muhamad Iqbal (2013)
There are several factors that influence the way students sit such as ergonomic factor, furniture specification and health issues. There have been many researches done on sitting postures related to ergonomic factors and health issues. However, this kind of study is still lacking in Malaysia. A study was conducted to determine the significance of UiTM students' sitting postures, furniture specification, gender of students, and residency status of the students. A total of 218 respondents answered a set of questionnaire. All the respondents were divided into 2 categories. Those categories are gender and residency. The data were analyzed using ANOVA method, which from the result, there are significant difference for the ten sitting aspects that were studied in this research and gender and residency status of students. From this research, all aspects that have been focused on the study have no significance with two factors being in focus.